2014
DOI: 10.1167/iovs.12-10457
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Estrogen and Androgen on Tear Secretion and Matrix Metalloproteinase-2 Expression in Lacrimal Glands of Ovariectomized Rats

Abstract: Citation: Song X, Zhao P, Wang G, Zhao X. The effects of estrogen and androgen on tear secretion and matrix metalloproteinase-2 expression in lacrimal glands of ovariectomized rats. Invest Ophthalmol Vis Sci. 2014;55:745-751. DOI:10.1167/iovs. 12-10457 PURPOSE. Previous studies have shown that ovariectomy (OVX) induces lacrimal gland regression and that androgens are implicated. This study explored the effects of estrogen and androgen on tear secretion and matrix metalloproteinase 2 (MMP-2) expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…Cell adhesion and proliferation were similar for cells incubated in medium containing any Ca 2+ level in the range of 4-12 mg/dL. On the other hand, cell viability was significantly decreased by incubation in medium containing [8][9][10][11][12] 30) and Berridge et al reported the high Ca 2+ levels can lead to cell death. 31) Taken together, these findings suggest that the viability of corneal epithelium cells is decreased under high Ca 2+ conditions (over 8 mg/dL) as are observed in the lacrimal fluid of OVX rats, and that a decrease in the viability of corneal epithelial cells may be the cause of delay in corneal wound healing in OXV rats.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Cell adhesion and proliferation were similar for cells incubated in medium containing any Ca 2+ level in the range of 4-12 mg/dL. On the other hand, cell viability was significantly decreased by incubation in medium containing [8][9][10][11][12] 30) and Berridge et al reported the high Ca 2+ levels can lead to cell death. 31) Taken together, these findings suggest that the viability of corneal epithelium cells is decreased under high Ca 2+ conditions (over 8 mg/dL) as are observed in the lacrimal fluid of OVX rats, and that a decrease in the viability of corneal epithelial cells may be the cause of delay in corneal wound healing in OXV rats.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the decrease in estrogen secretion following menopause is related to the prevalence of several disorders within the area innervated by the trigeminal nerve. 9,10) The ocular surface is an integrated unit comprising the corneal and conjunctival epithelia, meibomian glands, main and accessory lachrymal glands, and trigeminal neurons. It has been reported that a decrease in estrogen level results in dry eye in animal models.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, high level of E 2 was reported to cause increased anterior tibia dislocation in rats during pregnancy (Charlton et al, 2001). The mechanisms underlying E 2 and P 4 effects on knee laxity are not well understood, however evidences suggested that these effects could be mediated via changes in collagen turnover (Song et al, 2014), modulation of enzymes activity involved in collagen metabolism (Shan et al, 2013) as well as response of tissues toward relaxin via changes in the amount of receptor expressed (Dehghan et al, 2014a,b).…”
Section: Introductionmentioning
confidence: 99%